A framework to assess the vulnerability of estuarine systems for use in ecological risk assessment. (January 2016) - Ribeiro, D.C.; Costa, S.; Guilhermino, L.
Abstract: Estuaries are among the most pressured ecosystems, including by environmental contaminants resulting from anthropogenic activities, alterations due to global changes, and invasions by exotic species. The ecological risk assessment (ERA) of these pressures in complex ecosystems such as estuaries is often challenging and methods for the improvement of the process are need. Thus, the goal of the present study was to develop a general framework to assess the system vulnerability for use in the Problem Formulation phase of ERA in estuaries and other coastal ecosystems. This framework, is based on the multi-metric index approach and incorporates both inter- and intra-system analysis. It delivers information on the system's vulnerability, identifies especially vulnerable/affected zones of the system (spatial discretization) and the most critical period(s) for contamination events (temporal discretization). The framework was tested using the Minho River estuary as a case study, for both continental and offshore contamination events potentially affecting the system. The intra-system analysis revealed that the Minho estuary is the third most vulnerable system among those included in the study (nine systems of the north-west Iberian coast). The inter-system analysis was able to discriminate water-bodies with different vulnerability scores regarding existing contamination from continental origin, and offshore potential contamination events. The temporal analysis indicated July to September as the most vulnerable period in relation to both continental and offshore contamination. Thus, the application of this novel framework to the problem formulation of ERA may considerably improve the process in complex systems, such as estuaries and other coastal areas. Highlights: A framework to increase the accuracy of ERA's problem formulation phase was produced. It defines geographical and temporal vulnerability to contamination of a system. Vulnerability to both continental of offshore contamination scenarios was tested. The framework was tested in Minho estuary but can be applied to any aquatic system.